Prediksi Populasi dengan Matriks Leslie untuk Pemetaan Pemberdayan Perempuan - Sindi; Yurika Permanasari (Jurnal Riset Matematika, 2022)
Abstract. One of the Garut Regency government programs is to manage population growth and empower women, since the role of women is very important for population growth. The main objective of this study is to model and predict the number of female populations in Garut Regency in 2025. The method used in this study is to use the Leslie matrix. The results of modeling predicted that the number of female populations in Garut Regency in 2025 tend to increase. The prediction results for 2025 are 238,710 people for FAD targets, 333,832 people for KIRANA and SIGEMAR REHAT targets, 448,307 people for PUSPAGALING and GEMMAS KB targets, 301,324 people for GESSIT targets, 119,351 people for GERBANG LUNGGUH targets, and 270,549 women have not entered the program age. Abstrak. Salah satu program pemerintah kabupaten Garut adalah untuk mengedalikan pertumbuhan penduduk dan pemberdayaan perempuan, mengingat peran perempuan sangat penting bagi pertumbuhan populasi di masa depan. Tujuan utama dari penelitian ini adalah untuk memodelkan dan memprediksi jumlah populasi perempuan di kabupaten Garut pada tahun 2025. Metode yang digunakan dalam penelitian ini adalah dengan menggunakan matriks Leslie. Dari hasil pemodelan, diprediksi bahwa jumlah populasi perempuan di kabupaten Garut pada tahun 2025 cenderung meningkat. Hasil prediksi tahun 2025 sebesar 238.710 orang sasaran FAD, 333.832 orang sasaran KIRANA dan SIGEMAR REHAT 448.307 orang sasaran PUSPAGALING dan GEMMAS KB, 301.324 orang sasaran GESSIT, 119.351 orang sasaran GERBANG LUNGGUH, serta belum masuk usia program sebesar 270.549 perempuan.